2015
DOI: 10.1021/acs.biochem.5b00150
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Structural Basis for Acyl-Group Selectivity and NAD+ Dependence in Sirtuin-Catalyzed Deacylation

Abstract: Acylation of lysine is an important protein modification regulating diverse biological processes. It was recently demonstrated that members of the human Sirtuin family are capable of catalyzing long-chain deacylation, in addition to the well-known NAD+-dependent deacetylation activity.1 Here we provide a detailed kinetic and structural analysis that describes the interdependence of NAD+ and acyl-group length for a diverse series of human Sirtuins, SIRT1, SIRT2, SIRT3 and SIRT6. Steady-state and rapid-quench ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
230
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(245 citation statements)
references
References 49 publications
(129 reference statements)
12
230
1
2
Order By: Relevance
“…These findings are in keeping with the presence of nuclear metabolic territories as recently predicted (41,42) and prompted us to investigate whether nuclear NADH distribution could be influenced by SIRT1. Importantly, the K m of SIRT1 for NAD + seems to fall into the physiological range of NAD + bioavailability in the nucleus (43).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in keeping with the presence of nuclear metabolic territories as recently predicted (41,42) and prompted us to investigate whether nuclear NADH distribution could be influenced by SIRT1. Importantly, the K m of SIRT1 for NAD + seems to fall into the physiological range of NAD + bioavailability in the nucleus (43).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular Modeling; Structural Basis for Deacylation and NADH Inhibition-The findings that SIRT1-3 and SIRT6 can remove long-chain acyl groups prompted us to investigate the molecular basis for accommodation of long acyl-amide substrates in the active sites of sirtuins 1-3 and 6. The active sites of SIRT2 and -6 have been recognized to contain a hydrophobic pocket accommodating the long acyl chain of a myristoylated peptide (18,68) that is distinct from the NAD ϩ cofactor binding site (75). Based on published x-ray crystal structures, we analyzed the hydrophobicity of the active sites of SIRT1-3 and SIRT6 and found that a hydrophobic pocket was also present in SIRT1 and SIRT3 (Fig.…”
mentioning
confidence: 99%
“…Importantly, of the seven sirtuins encoded in the human genome, only Sirt1, -2, and -3 have a robust deacetylase activity. The other sirtuins have preferences for longer acyl chains (56,57).…”
mentioning
confidence: 99%